FROM LOYALTY TO ADVOCACY: THE MEDIATING ROLE OF INSTITUTIONAL IDENTIFICATION ON STUDENT CITIZENSHIP BEHAVIOR IN INDONESIAN HIGHER EDUCATION - Iskandar Arifin; Mirandha Ariesca Riana (RADJA PUBLIKA, 2026)
This study examines the mediating role of institutional identification between brand loyalty and Student Citizenship Behavior (SCB) in Indonesian higher education. Using a quantitative design with 350 student respondents and PLS-SEM analysis, findings reveal that brand loyalty significantly impacts institutional identification (β=0.750) and SCB (β=0.247). Crucially, institutional identification partially mediates this relationship (VAF=63.8%), effectively amplifying loyalty's impact on SCB. Validating Social Identity Theory, this study establishes institutional identification as the key